(Pro)cambium formation and proliferation: two sides of the same coin?. (February 2015) - Jouannet, Virginie; Brackmann, Klaus; Greb, Thomas
Highlights: (Pro)cambium cells give rise to vascular tissues and form a reticulate meristem pervading the whole plant body. In the root, the procambium arises from oriented and coordinated cell divisions, controlled by a mutual interaction between auxin and cytokinin signaling. Cambium proliferation is regulated by a system involving extensive intercellular communication. Currently, established regulatory networks initiating procambium cell identity and controlling cambium proliferation are barely connected. Abstract : The body of higher plants is usually pervaded by the (pro)cambium, a reticulate system of meristematic cells harboring the potential for producing vascular tissues at critical times and places. The (pro)cambium thereby provides the basis for the differential modulation of long-distance transport capacities and plant body stability. Distinct regulatory networks responsible for the initiation and proliferation of (pro)cambium cells have been identified. However, although a tight interaction between these networks can be expected, connections have been established only sporadically. Here we highlight recent discoveries of how (pro)cambium development is regulated and discuss possible interfaces between networks regulating two processes: (pro)cambium formation and cambium proliferation.